Pengembangan Instrumen Tes Fisika Berbasis Multirepresentasi Pada Materi Gerak Melingkar - Fitria, Wardatul; Syafrizal, Syafrizal; Halimatussakdiah, Halimatussakdiah; Fatmi, Nuraini; Ayunda, Desy Sary (Program Studi Pendidikan Fisika Universitas Katolik Widya Mandira, 2025)
The multirepresentation ability of students at SMA N 2 Bireuen and SMA N 3 Bireuen is still very low based on the results of observations and interviews as well as the distribution of questionnaires to students and several physics teachers at the schools studied. This study aims to develop a multirepresentation-based physics test instrument on circular motion material, which is used as a tool for students' multirepresentation abilities and meets the eligibility criteria of validity, reliability, difficulty level, and item discrimination. The type of research used in this study is Research and Development (R&D) which uses the ADDIE development model, which uses five stages, namely (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. The results of students' multirepresentation abilities found that students were able to answer questions in the very low category 0%, low category 48.75%, medium category 36.25%, and high category 15%. So, it can be concluded that the percentage of students who have the ability to answer multirepresentation questions on average is still relatively low.